Natural Compounds in Moringa oleifera Leaves Targeting Estrogen Receptor Beta (ESR2) for PCOS treatment: Insight from In Silico Docking - Aslikh Lana Dina; Alin Robiah Al Adawiah; Ade Hilman Juhaeni (Pusat Penelitian dan Pengembangan Bioteknologi dan Biodiversitas (P3BB) LPPM UNS, 2026)
Polycystic ovary syndrome (PCOS) is a health complication that often leads to infertility in women. PCOS, as a reproductive-metabolic disorder, is also related to breast cancer and other diseases. Nevertheless, there is no universal drug for PCOS treatment. Hence, exploring a new candidate’s drugs is crucial. Estrogen receptor beta (ESR2) has become a significant marker for PCOS and has the potential to be used as a target for PCOS treatment. This study aims to explore the potential use of moringa as a nutraceutical. This study provides in silico data of selected compounds (naringenin, gallic acid, quinic acid, quercetin, apigenin, and kaempferol) in moringa leaves as a candidate drug for PCOS treatment targeting ESR2. Naringenin and apigenin showed a noteworthy calculated binding affinity score from docking into ESR2 (<- 7kcal/mol). Protein-protein analysis and gene analysis showed that ESR2 is expressed in varying tissues. It strengthens the potential use of moringa as a nutraceutical. This study showed that Moringa leaves have the potential to be used as a complement to PCOS treatment.